2014
DOI: 10.1179/2042618614y.0000000077
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two non-thrust mobilization techniques applied to the C7 segment in patients with restricted and painful cervical rotation

Abstract: Objectives: Cervical mobilization and manipulation have been shown to improve cervical range of motion and pain. Rotatory thrust manipulation applied to the lower cervical segments is associated with controversy and the potential for eliciting adverse reactions (AR). The purpose of this clinical trial was to describe two translatory non-thrust mobilization techniques and evaluate their effect on cervical pain, motion restriction, and whether any adverse effects were reported when applied to the C7 segment. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…CT junction mobilizations delivered in this study could have reduced the stiffness at this segment and increased the overall cervical ROM. The increase in cervical ROM (in degrees) is almost equivalent to the previous studies after a single session of CT junction mobilization [ 8 , 11 ]. The thoracic manipulation group received treatment to an adjacent interdependent spinal region and demonstrated improvements in the study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…CT junction mobilizations delivered in this study could have reduced the stiffness at this segment and increased the overall cervical ROM. The increase in cervical ROM (in degrees) is almost equivalent to the previous studies after a single session of CT junction mobilization [ 8 , 11 ]. The thoracic manipulation group received treatment to an adjacent interdependent spinal region and demonstrated improvements in the study.…”
Section: Discussionsupporting
confidence: 80%
“…Improving the mobility of the CT junction reduces the demand for movement in the mid and lower cervical segments, thereby reducing the stress on the cervical spine. In addition, CT junction has been considered a safe segment to perform mobilizations in neck pain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MT treatment: The protocol consisted of a combination of ten techniques applied on the cervical, suboccipital, and temporomandibular areas: (1) neck accessory mobilization technique on C7 vertebra [16]; (2) mobilization neck central with posterior-anterior C5 vertebra mobilization [15];…”
Section: Interventionsmentioning
confidence: 99%
“…In this regard, a relationship between TMD and cervical dysfunction (one of the major goals of MT techniques) has been highlighted by several authors, explained by the topographic arrangement between the cervical spine and the trigeminal nerve [14]. Thus, upper neck mobilization has been shown to reduce pain and improve mobility of the craniocervical region in subjects with TMD [15,16]. In line with this, it has been reported that soft tissue manipulative treatment in suboccipital trigger points [17] and in the TMJ region improve muscle function, joint movement, and pain [18].…”
Section: Introductionmentioning
confidence: 99%